Integrating Student Programs to Encourage Emotional Intelligence: A Holistic Approach in School - Misbahol Jannah; Shafa Maliya Fitriyah Sumarhum; Ahmad Walid (Al-Qalam Institue, 2024)
This study explores the role of leadership in building a quality culture based on local wisdom at school.. The primary objective is to identify effective strategies and approaches for integrating local values into the school curriculum and programs. Utilizing a qualitative descriptive approach, data were collected through participatory observation, in-depth interviews, and documentation at SMA Negeri 1 Pakong, Pamekasan, East Java. The thematic analysis method was employed to analyze the data, revealing that effective leadership significantly enhances the integration of local cultural values in education. The findings indicate that leadership which involves collaboration between school and parents, enhances not only academic achievements but also character and moral development of students. This holistic approach ensures the sustainability of quality culture in schools. The study concludes that leadership plays a pivotal role in fostering an inclusive and supportive learning environment, which is crucial for the holistic development of students.